(3CfSGH GdCTQGa hCNHGQges - (3CHh GdMSf CMeO Hf jMji Hf LGHQ Hf OGhO, GdHdGPQj,J (B279 (3g` s
(3ChdgG (B:s
(3jHOC HNHQ ai CjGe YHO Gdedc QhGjI GdMLGL Hf jhSa GdYQGb MOKfi YHGS Hf gTGe Ke hdi YHO Gdedc GdMLGL Hf jhSa GdYQGb s
(3BNQgG (B:s
(3jfJgi HfSH Sge Hf YeQh Hf gUjU s
(3HgG fXGe GdJYbjHIs
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B267s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdJGQjNs